Behavior of 1-Deoxy-, 3-Deoxy- and N-Methyl-Ceramides in Skin Barrier Lipid Models - Kováčik, Andrej; Pullmannová, Petra; Pavlíková, Ludmila; Maixner, Jaroslav; Vávrová, Kateřina (Scientific reports, 2020)
Ceramides (Cer) are essential components of the skin permeability barrier. To probe the role of Cer polar head groups involved in the interfacial hydrogen bonding, the N-lignoceroyl sphingosine polar head was modified by removing the hydroxyls in C-1 (1-deoxy-Cer) or C-3 positions (3-deoxy-Cer) and by N-methylation of amide group (N-Me-Cer). Multilamellar skin lipid models were prepared as equimolar mixtures of Cer, lignoceric acid and cholesterol, with 5 wt% cholesteryl sulfate. In the 1-deoxy-Cer-based models, the lipid species were separated into highly ordered domains (as found by X-ray diffraction and infrared spectroscopy) resulting in similar water loss but 4-5-fold higher permeability to model substances compared to control with natural Cer. In contrast, 3-deoxy-Cer did not change lipid chain order but promoted the formation of a well-organized structure with a 10.8 nm repeat period. Yet both lipid models comprising deoxy-Cer had similar permeabilities to all markers. N-Methylation of Cer decreased lipid chain order, led to phase separation, and improved cholesterol miscibility in the lipid membranes, resulting in 3-fold increased water loss and 10-fold increased permeability to model compounds compared to control. Thus, the C-1 and C-3 hydroxyls and amide group, which are common to all Cer subclasses, considerably affect lipid miscibility and chain order, formation of periodical nanostructures, and permeability of the skin barrier lipid models.
Keywords: voda; Permeability; Phase Transition; Membranes, Artificial; permeabilita; Cell Membrane; Ceramides; změna skupenství; Skin; kůže; ceramidy; Water; membrány umělé; buněčná membrána